2022
DOI: 10.1002/ags3.12588
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for non‐gastric‐cancer‐related death after gastrectomy in elderly patients

Abstract: Aim: To identify preoperative factors, especially other diseases that cause death, that are associated with the prognosis of gastrectomy in elderly patients with gastric cancer.Methods: This retrospective study included a total of 211 consecutive patients aged ≥75 years who underwent radical gastrectomy due to gastric cancer. Time-dependent receiver operating characteristic curve analysis was performed to determine the optimal cutoff values for various perioperative factors. Risk factors for the overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The escalating incidence of gastric cancer among the elderly, reflective of broader demographic shifts towards an aging population, presents unique clinical challenges [ 1 3 ]. This demographic shift not only intensifies the complexities inherent in managing elderly patients but also necessities a nuanced understanding of the multifactorial nature of their health outcomes, particularly the elevated incidence of non-cancer-related mortality post-surgery [ 2 , 7 9 ]. Previous research has identified individual risk factors such as sex, neutrophil-to-lymphocyte ratio, and skeletal muscle mass index [ 6 ], but did not fully address their collective impact on mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The escalating incidence of gastric cancer among the elderly, reflective of broader demographic shifts towards an aging population, presents unique clinical challenges [ 1 3 ]. This demographic shift not only intensifies the complexities inherent in managing elderly patients but also necessities a nuanced understanding of the multifactorial nature of their health outcomes, particularly the elevated incidence of non-cancer-related mortality post-surgery [ 2 , 7 9 ]. Previous research has identified individual risk factors such as sex, neutrophil-to-lymphocyte ratio, and skeletal muscle mass index [ 6 ], but did not fully address their collective impact on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A major concern in the post-surgical management of elderly gastric cancer patients is the incidence of non-cancer-related fatalities. Previous study have identified key preoperative factors like sex, neutrophil-to-lymphocyte ratio, and skeletal muscle mass index as significant risk factors for non-cancer-related death in this patient group [ 7 ]. Despite these insights, a considerable number of elderly patients undergoing curative resection still succumb to non-cancer-related fatalities [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative parameters. All perioperative parameters were assessed and calculated following the methodology outlined in the authors' previous study (9). In summary, demographic information (age and gender), comorbidity data [modified frailty index (mFI) (10) and Charlson comorbidity index (CCI)], and performance status (PS) data were extracted from medical records.…”
Section: Methodsmentioning
confidence: 99%
“…In this issue of the Annals of Gastroenterological Surgery , Iida et al reported the risk factors for non‐gastric‐cancer‐related death after gastrectomy in elderly patients. 1 The risk factors for non‐gastric‐cancer‐related death and overall survival of patients aged ≥75 years who undergo radical gastrectomy are male gender, low skeletal muscle mass index (SMI), and high neutrophil‐to‐lymphocyte ratio (NLR). According to the Report of the National Clinical Database 2011‐2019, 16.8% of the patients who underwent a distal gastrectomy in 2011 were aged 75‐80 years, and 18.5% were aged ≥80 years compared to 19.3% aged 75‐80 years and 24.3% aged ≥80 years in 2019.…”
mentioning
confidence: 99%
“…In this issue of the Annals of Gastroenterological Surgery , Iida et al reported the risk factors for non‐gastric‐cancer‐related death after gastrectomy in elderly patients 1 . The risk factors for non‐gastric‐cancer‐related death and overall survival of patients aged ≥75 years who undergo radical gastrectomy are male gender, low skeletal muscle mass index (SMI), and high neutrophil‐to‐lymphocyte ratio (NLR).…”
mentioning
confidence: 99%